Review of Patents on Small Grinding Wheel Polishing Technology - Li, Guo; Zhu, Kuntan (Recent Patents on Engineering, 2024)
Grinding disc polishing is an important polishing method that can be used to manufacture various high-precision and high-quality optical components. The smoothing effect of grinding discs is a simple and effective method widely used to suppress MSF errors. Grinding disc technology has good polishing effects on flat, spherical, aspherical, and free form surfaces. The polishing mechanism is to generate chips through the small plastic cutting of abrasive particles, but it only uses a very small amount of abrasive particles to exert force and uses the flow friction between the abrasive particles and the grinding disc and the workpiece to flatten the surface roughness of the workpiece. It can be seen from the relevant literature that the floating tool holder maintains a constant pressure to solve the problem of uneven pressure distribution between optical components. The adjustable tool holder can adjust the amount of spring deformation to adapt to local surface changes of optical parts, ensuring consistent material removal. The force-adaptive tool holder can be adjusted in real time during the machining process to reduce errors generated during machining. The jointed tool holder improves the fit between the grinding wheel and optical components, ensuring a tight fit between the grinding wheel and optical components. This patent paper aims to introduce grinding wheel polishing technology as an essential method for manufacturing high-precision, high-quality optical components. It explores the optimization of abrasive tool design and the improvement of processing efficiency and proposes suggestions and prospects for future research, applications, and development. Through querying literature and patent databases, patent documents related to grinding disc polishing technology were collected and analyzed. The design characteristics of the device structure, technological innovations, as well as the effectiveness and improvements in practical applications were focused. Grinding disc polishing technology effectively removes surface defects and enhances the optical performance of optical components, particularly in suppressing MSF errors. This technology is suitable for flat, spherical, non-spherical, and freeform surfaces, with broad potential applications. Despite the numerous advantages of grinding disc polishing technology, such as simplicity, effectiveness, and wide applicability, critical issues still need to be addressed, including surface morphology control, improving polishing efficiency, and enhancing consistency. Future research should focus on optimizing tool design and developing new polishing materials and processes to improve the manufacturing quality and efficiency of optical components.
Keywords: optical components